Temporal changes in the markers of ribosome biogenesis in rat soleus muscle under simulated microgravity. (September 2021) - Rozhkov, Sergey V.; Sharlo, Kristina A.; Mirzoev, Timur M.; Shenkman, Boris S.
Abstract: Skeletal muscle inactivity due to real or simulated microgravity results in a significant atrophy of muscle fibers. One of the key causes of disuse atrophy is a decrease in the rate of muscle protein synthesis (MPS). MPS is dependent not only on translational efficiency but also on the number of ribosomes available for translation (translational capacity), however a time course for biomarkers of ribosome biogenesis during muscle disuse remains understudied. The aim of the study was to analyze temporal changes in the regulators/markers of ribosome biogenesis in rat soleus muscle during the course of disuse. Rats were subjected to hindlimb unloading (HU) for 1, 3, 7 and 14 days. 18S + 28S rRNA content was assessed by gel-electrophoresis; expression levels of 45S pre-rRNA and c-Myc were determined by RT-PCR and the rate of MPS was measured using SUnSET method. The content of 18S + 28S rRNA and total RNA as well as 45S pre-rRNA expression significantly decreased after 1-day HU and remained diminished for the entire unloading period. c-Myc mRNA expression was downregulated following 1, 3 and 7 days of HU, but did not significantly differ from control after 14-day HU. MPS showed a progressive decrease from the 3rd to 14th day of HU. Thus, a decrease in MPS in rat soleus during 3-, 7- and 14-day HU was accompanied by downregulation of the key markers of translational capacity. Highlights: The study revealed temporal alterations in ribosome biogenesis in rat soleus muscle during simulated microgravity. A decrease in 45S pre-rRNA expression in rat soleus was observed at both early and later stages of simulated microgravity. A decline in 18S+28S rRNA and total RNA in rat soleus was detected after 1, 3, 7 and 14 days of simulated microgravity. A significant reduction in c-Myc expression in rat soleus was observed following 1, 3 and 7 days of simulated microgravity.